Correction: IL-17 mediates protective immunity against nasal infection with Bordetella pertussis by mobilizing neutrophils, especially Siglec-F+ neutrophils - Mills, Kingston (My University, 2021)
The original version of this article unfortunately contained a mistake in Fig. 3h. Due to a typesetting error the lines on the graph have been moved below the X axis. We apologize for this error. The correct Fig. 3h can be found below. The original article has been corrected. https://doi.org/10.1038/s41385-021-00407-5
Keywords: Correction; IL17; Graph